Brain plasticity of rats exposed to prenatal immobilization stress - Abrahamyan, S.S.; Meliksetyan, I.B.; Sahakyan, I.K.; Tumasyan, N.V.; Badalyan, B.Yu.; Galoyan, A.A. (Вiopolymers and Cell, 2011)
Aim. This histochemical and immunohistochemical study was aimed at examining the brain cellular structures of newborn rats exposed to prenatal immobilization (IMO) stress. Methods. Histochemical method on detection of Ca2+-dependent acid phosphatase activity and ABC immunohistochemical technique. Results. Cell structures with radial astrocytes marker GFAP, neuroepithelial stem cell marker gene nestin, stem-cells marker and the hypothalamic neuroprotective proline-rich polypeptide PRP-1 (aka Galarmin, a natural cytokine of a common precursor to neurophysin vasopressin associated glycoprotein) have been revealed in several brain regions. Conclusions. Our findings indicate the process of generation of new neurons in response to IMO and PRP-1 involvement in this recovery mechanism, as PRP-1-Ir was detected in the above mentioned cell structures, as well as in the neurons and nerve fibers. Keywords: rat brain plasticity, prenatal immobilization stress, GFAP-, nestin-, stem cells-, and PRP-1-immunoreactive structures.